Student Management and Information System (International Journal of Scientific Research in Science and Technology, 2024)
Managing student-related information in educational institutes becomes more cumbersome each year. As all systems today are being computerized, there is a need for an automated system to manage such information effectively. This paper proposes the development of a Student Management and Information System (SMIS) that computerizes the management of student activities and data. The system is user-friendly, efficient, and cost-effective, handling student academic and non-academic details, hostel management, leave management, and more. SMIS provides a simple graphical interface for maintaining student details.